Navigating acculturative stress: A phenomenological study of the lived experiences of international students in Pakistan - Akram Riaz, Muhammad; Rafique, Rafia; Riaz, Muhammad Naveed (Journal of International Students, 2026)
A considerable number of international students are enrolled in Pakistani universities. This research seeks to examine the psychological experiences of international students in Pakistan. A meticulously chosen cohort of overseas students engaged in semi-structured interviews. Data were gathered from six different institutions in Pakistan. The data analysis used the interpretative phenomenological analysis as outlined by Smith et al. (2009). The research identified ten prominent themes among individuals facing mental health challenges: perceived cultural disparities, communication barriers, academic difficulties, social hindrances, psychological issues, physical health problems, diminished life satisfaction, lowered self-esteem, financial limitations, and insufficient coping strategies. The international students having better mental health were identified with ten significant themes: perceived cultural disparities, communication obstacles, academic apprehensions, social issues, psychological challenges, increased life satisfaction, heightened self-esteem, perceived optimism, personal drive, and effective coping strategies. The findings have significant relevance for both practitioners and scholars involved with international students.